2003
DOI: 10.1016/s1097-2765(03)00173-4
|View full text |Cite
|
Sign up to set email alerts
|

Skp2 Regulates Myc Protein Stability and Activity

Abstract: Myc is an oncoprotein transcription factor that plays a prominent role in cancer. Like many transcription factors, Myc is an unstable protein that is destroyed by ubiquitin (Ub)-mediated proteolysis. Here, we report that the oncoprotein and Ub ligase Skp2 regulates Myc ubiquitylation and stability. Because of the growing number of Ub ligases that function as transcriptional coactivators, we speculated that Skp2 might also regulate Myc's transcriptional activity. Consistent with this model, we also show that Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
446
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 463 publications
(484 citation statements)
references
References 50 publications
35
446
3
Order By: Relevance
“…We found that N-MycWT could co-immunoprecipitate with TRRAP but that N-MycD73 could not, consistent with the finding that c-Myc-S is also defective for TRRAP binding (Figure 3a) (McMahon et al, 1998). Skp2 is an F-box protein which binds to MBII and stimulates Myc-dependent transactivation (Kim et al, 2003;von der Lehr et al, 2003). We found that N-MycWT binding to Skp2 is MBII dependent, however N-MycD73 is even more defective than N-MycDMBII for Skp2 binding (Figure 3a).…”
Section: C-myc-s-induced Proliferation Is Mbii-dependent Vh Cowling Asupporting
confidence: 84%
“…We found that N-MycWT could co-immunoprecipitate with TRRAP but that N-MycD73 could not, consistent with the finding that c-Myc-S is also defective for TRRAP binding (Figure 3a) (McMahon et al, 1998). Skp2 is an F-box protein which binds to MBII and stimulates Myc-dependent transactivation (Kim et al, 2003;von der Lehr et al, 2003). We found that N-MycWT binding to Skp2 is MBII dependent, however N-MycD73 is even more defective than N-MycDMBII for Skp2 binding (Figure 3a).…”
Section: C-myc-s-induced Proliferation Is Mbii-dependent Vh Cowling Asupporting
confidence: 84%
“…Several stem cell markers, including MyoD [51] and Myc [52], were previously shown to be regulated by protein stability modulation during cellular differentiation. Regulation of the scaffold protein, Sur8, by protein stability can control assembly of the Ras-ERK pathway members in response to signals controlling NPC differentiation and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The MB2 motif is required for the efficient interaction with several co-factors such as TRRAP and associated HATs (McMahon et al, 1998;Bouchard et al, 2001;Frank et al, 2001;Nikiforov et al, 2002), the HAT complex component BAF53 , TIP48 & TIP49 , Skp2 (Kim et al, 2003;von der Lehr et al, 2003), and for the stimulation of pre-mRNA capping (Cowling and Cole, 2007). Nevertheless, it has been shown that a Myc mutant lacking MB2 still efficiently activates the expression of some target genes and artificial reporters (Kato et al, 1990;BelloFernandez et al, 1993;Li et al, 1994;Brough et al, 1995;Lee et al, 1997;Xiao et al, 1998;Nikiforov et al, 2002), although many targets are only poorly activated by such a protein (Conzen et al, 2000;Hirst and Grandori, 2000;Bouchard et al, 2001;Nikiforov et al, 2002;Kenney et al, 2003;Cowling and Cole, 2007).…”
Section: To Molecularly Understand How Myc Controls Its Target Genes mentioning
confidence: 99%